2022
DOI: 10.1063/5.0129203
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ESRGAN for super-resolution reconstruction of turbulent flows with tricubic interpolation-based transfer learning

Abstract: Turbulence is a complicated phenomenon because of its chaotic behavior with multiple spatio-temporal scales. Turbulence also has irregularity and diffusivity, making predicting and reconstructing turbulence more challenging. This study proposes a deep-learning approach to reconstruct three-dimensional (3D) high-resolution turbulent flows from spatially-limited data using a 3D enhanced super-resolution generative adversarial networks (3D-ESRGAN). In addition, a novel transfer-learning method based on tricubic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…2021, 2022 b ; Yu et al. 2022). In a GAN model that is used for image generation, two adversarial neural networks called the generator () and the discriminator () compete with each other.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2021, 2022 b ; Yu et al. 2022). In a GAN model that is used for image generation, two adversarial neural networks called the generator () and the discriminator () compete with each other.…”
Section: Methodsmentioning
confidence: 99%
“…(Goodfellow et al 2014) have shown great success in image transformation and super-resolution problems (Mirza & Osindero 2014;Ledig et al 2017;Zhu et al 2017;Wang et al 2018). Generative adversarial network-based models have also shown promising results in reconstructing HR turbulent flow fields from coarse data (Fukami et al 2019a;Fukami, Fukagata & Taira 2021;Güemes et al 2021;Kim et al 2021;Yousif et al , 2022bYu et al 2022). In a GAN model that is used for image generation, two adversarial neural networks called the generator (G) and the discriminator (D) compete with each other.…”
Section: Masked Multiheadmentioning
confidence: 99%
See 1 more Smart Citation
“…A convolutional neural network (CNN) is used for predicting the velocity field, as discussed by Schmekel et al [30]. Note that CNNs and other computer-vision architectures have been successfully used in the context of turbulent-flow predictions [28,[58][59][60][61]. The convolution operation is described by Equation ( 4), where f is the input three-dimensional (3D) tensor, h the filter, G the output, and m, n and p the indices of the output tensor:…”
Section: Deep-neural-network Architecture and Predictionmentioning
confidence: 99%
“…2021; Yu et al. 2022; Yousif et al. 2023 a ), where deep learning is a subset of machine learning, in which neural networks with multiple layers are used in the model (LeCun, Bengio & Hinton 2015).…”
Section: Introductionmentioning
confidence: 99%